Analisis Implementasi Perubahan Pembelajaran Daring Terhadap Kebijakan Publik Di Indonesia - Sari, Cindy Fatika; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
The change in the learning policy system during the COVID-19 pandemic that was implemented by the government into an online process using electronic media due to the temporary closure of educational institutions that occurred in Indonesia was no exception. This has become one of the most influential disturbances in the education system, which previously implemented a face-to-face psychic system for both students and teachers. Therefore, the burden borne by each element of special education by the government is getting bigger in facilitating schools and educational institutions to prepare for a good future of education in order to reduce losses in the world of education in the future